Studying of cyp2c19*2, *3 and *17 polymorphism in Vietnamese patients with coronary artery disease - Hai Ha, Nguyen; Bich Thao, Le Thi; Thanh Hoa, Nguyen Thi; Thu Hien, Le Thi (Vietnam Journal of Biotechnology, 2020)
Coronary artery disease is the most common type of cardiovascular disease, due to the accumulation of atherosclerotic plaque inside the arterial wall which leads to block blood supply to the heart muscle. A number of clinical trials have demonstrated that Clopidogrel is able to inhibit platelet aggregation in patients with acute coronary syndromes, reduce mortality and cardiovascular events. However, the antiplatelet effectiveness of Clopidogrel significantly depends on CYP2C19 genotypes. Therefore, the aim of this study was to identify the CYP2C19*2, *3 and allele frequencies in Vietnamese coronary artery patients by using PCR-RFLP method. Total genomic DNA were extracted from peripheral blood of 96 patients diagnosed with coronary artery disease. Thereafter, single nucleotide polymorphism sites in the CYP2C19 gene were identified by PCR with specific primers. The amplified products were then digested by restriction enzymes SmaI, BamHI, and MnlI, respectively. The results showed that the proportion of heterozygous individuals for CYP2C19*2 (c. 681G>A, rs4244285), CYP2C19*3 (c. 636G>A, rs4986893), and CYP2C19*17 (g. -3402C>T, rs11188072) accounted for 39.58%, 6.25%, and 2.08%, respectively. Among 96 subjects, 41.67% of patients were predicted for intermediate metabolic phenotype CYP2C19*1/*2 (37.50%) and CYP2C19*1/*3 (4.17%). Approximately 10.42% of total patients represented poor metabolizers in which 8.34% had two copies of the same allele *2/*2 and 2.08% had *2/*3 genotype. Particularly, two individuals (2.08%) detected with CYP2C19*1/*17 genotype were able to increase CYP2C19 activity (ultrarapid metabolizers). The results of this study generate a foundation for introducing individualized antiplatelet therapy in Vietnam based on genetic testing.